High efficient removal of bisphenol A in a peroxymonosulfate/iron functionalized biochar system: Mechanistic elucidation and quantification of the contributors - Jiang, Shun-Feng; Ling, Li-Li; Chen, Wen-Jing; Liu, Wu-Jun; Li, De-Chang; Jiang, Hong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
The new and low-cost iron embedded carbon composites (Fe-BC-700) were prepared by a facile pyrolysis technology. The as-prepared material exhibited an extremely high removal efficiency of biphenol A in the presence of peroxymonosulfate (PMS). Besides the sulfate radicals (SO4−) from the PMS activation, the inherent persistent free radicals (PFR) in biochar also played an important role in the degradation of BPA. [Display omitted] •Fe-BC-700 with Fe0, abundant functional groups and nanofibers was facilely prepared.•The high removal efficiency of BPA depends on activation and non-activation factors.•The contribution of the different factors was quantified for the first time. Activation of peroxymonosulfate (PMS) to degrade recalcitrant organic pollutants has attracted much attention, however, this process usually needs expensive or toxic catalysts. Herein, we prepared a Fe functionalized biochar composite that contain Fe0, porous carbon with abundant functional groups and nanofibers (Fe-BC-700) to activate PMS and efficiently remove bisphenol A (BPA). The contribution of different participants in the complicated system involving Fe species, carbon composites, and radicals and nonradicals were quantitatively investigated. Under optimal conditions (0.2 g/L PMS and 0.15 g/L catalyst), 20 mg/L of BPA can be completely removed in 5 min by Fe-BC-700. The effects including the activation of PMS by Fe species to produce sulfate radicals (SO4−), the electron transfer by the nanofiber-mesoporous carbon structure, and the inherent persistent free radicals (PFR) in biochar, were demonstrated to contribute to the high performance. A series of contrast experiments showed that PMS activated by Fe contributed to about 36% of BPA degradation, while the carbon composites, especially carbon nanofibers contributed to 17%, and the other 47% was ascribed to the adsorption of carbon composites (may further undergoing degradation). Meanwhile, the degradation by SO4− accounted for about 23% (by quenching experiments), while the nonradical pathway contributed to 30%. This work suggests that the non-activation factors in PMS/porous catalyst/pollutant system cannot be neglected.